Person-centered care approach to prevention and management of falls among adults and aged in a Brazilian hospital: a best practice implementation project. Issue 1 (14th March 2023) - Albertini, Anna Carolina da Silva; Fernandes, Renato Pinheiro; Püschel, Vilanice Alves de Araújo; Maia, Flavia de Oliveira Motta
ABSTRACT: Objectives: The objective is to assess compliance with evidence-based criteria regarding a person-centered care approach to the prevention and management of falls among adults and the elderly in a Brazilian private hospital. Methods: This project used the JBI audit and feedback method to implement evidence into practice. The JBI Practical Application of Clinical Evidence System and Getting Research into Practice audit tools have been used to promote changes in oncology and medical–surgical wards. The implementation protocol was designed based on the primary barriers and facilitators identified in the baseline audit, along with a training program and changes in the electronic medical records. Nursing documentation available in medical records, interviews with nurses who worked in oncology and medical–surgical wards, and interviews with patients admitted in oncology and medical–surgical wards were used to assess the baseline and follow-up audit compliance rates. Results: The baseline and follow-up audits showed improvement for criteria 3 and 9 (100%) and criteria 6 and 7 (97%), respectively. The compliance for criteria 4 (97.6%), 5 (76.7%), and 8 (18%) showed slight variations from baseline and follow-up audits. Compliance for criteria 1 (76.9%) and 2 (63.3%) decreased in the follow-up audit. Conclusion: These findings support that baseline, and follow-up audits allied to a fall training program and changes in the electronic nursing records increase the compliance rates related to evidence-based practice regarding a person-centered care approach to preventing and managing falls. We will implement new strategies according to the best practices to achieve better outcomes.